Critical Aspects of Metal–Organic Framework‐Based Materials for Solar‐Driven CO2 Reduction into Valuable Fuels. Issue 2 (25th November 2020) - He, Yiqiang; Li, Chunguang; Chen, Xiao‐Bo; Rao, Heng; Shi, Zhan; Feng, Shouhua
Abstract: Photoreduction of CO2 into value‐added fuels is one of the most promising strategies for tackling the energy crisis and mitigating the "greenhouse effect." Recently, metal–organic frameworks (MOFs) have been widely investigated in the field of CO2 photoreduction owing to their high CO2 uptake and adjustable functional groups. The fundamental factors and state‐of‐the‐art advancements in MOFs for photocatalytic CO2 reduction are summarized from the critical perspectives of light absorption, carrier dynamics, adsorption/activation, and reaction on the surface of photocatalysts, which are the three main critical aspects for CO2 photoreduction and determine the overall photocatalytic efficiency. In view of the merits of porous materials, recent progress of three other types of porous materials are also briefly summarized, namely zeolite‐based, covalent–organic frameworks based (COFs‐based), and porous semiconductor or organic polymer based photocatalysts. The remarkable performance of these porous materials for solar‐driven CO2 reduction systems is highlighted. Finally, challenges and opportunities of porous materials for photocatalytic CO2 reduction are presented, aiming to provide a new viewpoint for improving the overall photocatalytic CO2 reduction efficiency with porous materials. Abstract : Porous materials, including metal–organic frameworks, covalent organic frameworks, zeolites, and inorganic/organic porous semiconductors used for photocatalytic CO2 reduction are reviewed. Porous materials have been intensively exploited in solar‐driven CO2 reduction reactions for making valuable fuels. Three critical aspects of CO2 photoreduction are summarized and discussed, which provide new guidance for the future practical applications of porous materials.